The Nutrient Digestibility of Locally Sheep Fed with Amofer Palm Oil Byproduct-Based Complete Feed - Template Template (Chemical Engineering Diponegoro University)
Utilization of palm oil by-product such as palm fronds, leaves, empty fruit bunches (EFB), fiber fruit juice (FFJ), palm kernel cake (PKC), and palm oil sludge (POS) as the source of energy and protein for ruminants, especially sheep is an efficient effort to make a new opportunities in term of economical and beneficial product that will reduce environmental pollution. The objectives of this research were to analyze the effect of palm oil’s byproduct-based complete feed on sheep’s nutrient digestibility. Sixteen male sheeps of nine month old with average body weight 14.69+0.82 kg were used. The complete feed was formulated by ammoniated-fermented technology from palm fronds and leaves, EFB and FFJ, also Centrosema sp., PKC, POS, ground corn, rice bran, cassava, molasses, urea, mineral mix and salt. The complete feed with different levels of crude protein (CP) and TDN were used in this research which consisted of T1=10,63% CP; 63.46% TDN; T2=12.27% CP; 62.38% TDN; T3=13.70% CP; 64.11% TDN; and T4=15.90% CP; 61.28% TDN. The study used a completely randomized design (CRD) which consisted of four treatments and four replications. Data was analyzed using ANOVA with significance level at 95% and followed by Duncan Multiple Range Test. The experimental results showed that the protein level affected the feed digestibility. The highest digestibility of dry matter, organic matter and crude protein were 65.79%, 70.30%, and 84.34% respectively, resulting in 14% protein level (T3) were significantly different with treatment at protein level 10% (T1), 12% (T2) and 16% (T4) at p<0.05. It can be concluded that by-product of palm oil plantation and mill had good nutritional value. Therefore, this feedstuff can be used to formulate complete feed for sheep and it successfully increased the nutrient digestibility.